2005
DOI: 10.1007/s00403-005-0565-9
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband–UVB irradiation decreases the production of pro-inflammatory cytokines by stimulated T cells

Abstract: Narrow-band ultraviolet B (UVB) phototherapy is an effective treatment for psoriasis. Owing to its limited penetration, the direct effects of UVB are mostly restricted to cells residing in the epidermis and papillary dermis, and are associated with epidermal depletion of Langerhans' cells (LC) and T cells. It has been argued that the depletion of the skin-resident T-cell population may be due to a combination of UVB-induced apoptosis and decreased recruitment from the blood due to lower expression of the requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 25 publications
1
71
0
2
Order By: Relevance
“…Alternatively, activated T cells may continuously be recruited from circulation in patients after nb-UVB but not after biologics treatment. Taken the available data on circulating T cells during biologics (39,40) and nb-UVB treatment (41,42) it is not possible to predict whether replenishment of skin T cells occur in the different treatments. The inflammatory profiles in epidermal T cells may seem contradictory to previous publications where expression analysis of full skin biopsies 6 wk after nb-UVB treatment suggested normalization of IL17A and IL22 gene expression (43,44) and highlights the importance of dissecting different T cell populations present within the different anatomical compartments of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, activated T cells may continuously be recruited from circulation in patients after nb-UVB but not after biologics treatment. Taken the available data on circulating T cells during biologics (39,40) and nb-UVB treatment (41,42) it is not possible to predict whether replenishment of skin T cells occur in the different treatments. The inflammatory profiles in epidermal T cells may seem contradictory to previous publications where expression analysis of full skin biopsies 6 wk after nb-UVB treatment suggested normalization of IL17A and IL22 gene expression (43,44) and highlights the importance of dissecting different T cell populations present within the different anatomical compartments of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although its mechanism of action is not completely understood, it appears that NVUV-B has both anti-inflammatory and immunosuppressive effects. 7 While several reports and small case series have demonstrated the effectiveness of UV-A1 therapy (340-400 nm) for extragenital LS, 5,8,9 we could find no published studies in which NBUV-B (311-313 nm) was successfully or unsuccessfully used to treat this condition. Several studies have demonstrated that both UV-A1 and NBUV-B increase matrix-metalloproteinase levels in human skin and cultured dermal fibroblasts, 9-14 which may explain the effectiveness of UV-A1 in sclerosing skin diseases.…”
Section: Commentmentioning
confidence: 63%
“…In addition, NB-UVB inhibits the release of proinflammatory cytokines [10, 11] and the expression of intercellular adhesion molecule 1 [9, 12]. Finally, NB-UVB isomerizes urocanic acid with a strong downregulatory activity on T-cell functions [13].…”
Section: Discussionmentioning
confidence: 99%